The effect of hotel facilities and guest satisfaction on customer loyalty at the Sibayak Hotel Berastagi - Tambunan, Sontina Griche; Sihombing, Daniel (Trigin Publisher, 2026)
This study aims to determine: (1) the influence of hotel facilities on customer loyalty at the Sibayak Berastagi Hotel in Karo Regency. (2) the influence of guest satisfaction on customer loyalty at the Sibayak Berastagi Hotel in Karo Regency. (3) the influence of hotel facilities and guest satisfaction on customer loyalty at the Sibayak Berastagi Hotel in Karo Regency. This research approach is quantitative research using a questionnaire. The population in this study were 300 customers at the Sibayak Berastagi Hotel in July to September 2025. From a population of 300 customers using the Slovin formula and a significance level of 10%. Based on the calculation, a sample of 75 customers was obtained. Direct hypothesis testing was used with the F test and partially with the t test. Based on the results of the study are as follows: (1) Partially the first hypothesis states that there is an influence of hotel facilities on customer loyalty at the Sibayak Berastagi Hotel. (2) Partially the second hypothesis states that there is an influence of guest satisfaction on customer loyalty at the Sibayak Berastagi Hotel. (3) Simultaneously, hotel facilities and guest satisfaction together have a significant influence on customer loyalty at the Sibayak Berastagi Hotel. (4) The effective contribution generated is 0.651, meaning that 65.1% of the independent variables contribute an effective influence on the dependent variable, while the remaining 34.9% is influenced by other factors.